Melancholy Experience in Literature of the Long Eighteenth Century - Ingram, A. author. aut Link
IX, 246 p.
Keywords: Arising from a research project on depression in the eighteenth century, this book discusses the experience of depressive states both in terms of existing modes of thought and expression, and of attempts to describe and live with suffering. It also asks what present-day society can learn about depression from the eighteenth-century experience.